PENERAPAN ANALISIS MULTIDIMENSIONAL SCALING (MDS) PADA PEMETAAN KABUPATEN/KOTA DI PROVINSI SULAWESI TENGAH BERDASARKAN INDIKATOR TENAGA KESEHATAN - Islami, Mira Bela; Rais, Rais; Handayani, Lilies (Natural Science: Journal of Science and Technology, 2019)
Health workers is any person who dedicates theirself in the health sector and have knowledge, skills and authority to make health efforts. The lack number of health workers or the univen distribution of health workers is a problem that often occurs in each region. This research will use the method  of multidimensional scaling in mapping districts / cities in Central Sulawesi Province based on indicators of health workers. The results obtained are formed in to 4 groups of districts/cities that have similarities among its members but different from other groups. In the group 1 is Palu, Group 2 contained Parigi Moutong districts. In the group 3 consists of Banggai, Poso, Sigi and Toli-Toli Districts. In the group 4 consist of Tojo Una-una, Morowali, Donggala, Morowali Utara, Banggai Laut, Buol, and Banggai Islands. Stress value obtained is 4.354% and the value of R^2 is 99.568%, which indicates that the data used can be mapped properly.